Including homeless families and children in the social protection system: a brief review of international experience and an analysis of data on the Philippine pilot programme - Mendoza, Ronald U (Archīum Ateneo, 2014)
The Pantawid Pamilyang Pilipino Programme (4Ps) is one of the projects subsumed within the Philippine social protection agenda. The 4Ps, under the management of the Department of Social and Welfare and Development (DSWD), has covered over 7 million children belonging to approximately 3 million poor families with homes from the period February 2008 to May 2012. In an effort to extend social protection services to the homeless, the DSWD launched the Modified Conditional Cash Transfer for Homeless (MCCT-HSF) programme in the second half of 2012. The MCCT-HSF, viewed as an extension of the 4Ps, intends to provide immediate relief, support and services to homeless families. It is also designed as a mechanism through which homeless families can transition into the 4Ps. This study serves as a review of social protection programmes that are similar to the MCCT-HSF and as a preliminary analysis of the data gleaned from the pilot implementation of the MCCT-HSF. A review of the social protection programmes for the homeless of other countries suggests that the success of these kinds of programmes is contingent on the development of accurate integrated targeting, monitoring and delivery systems. Moreover, it has been observed that the construction of cost-effective transient housing facilities or temporary shelters, and the provision of personalized psychosocial counselling services are instrumental to the success of homeless protection programmes for the homeless. The data from the MCCT-HSF pilot implementation indicate that homeless families found in Metro Manila originate from poor regions that are close to the National Capital Region. The data set also reveals that most of the homeless included in the pilot implementation attained only an elementary-level education. A considerable proportion of the homeless is either unemployed or employed in the informal sector.